Application of the Sustainable Business Model Framework: Evidence from a Multinational Company. - Devine, Åsa; Sandell, Michaela (European Journal of Sustainable Development, 2023)
All organizations are unique, not least considering when and how certain sustainable business practices are initiated and managed. Organizations therefore need an instrument that is possible to adapt to allow for monitoring sustainability progress. In the Sustainable Business Model (SBM) framework, developed by the authors, the sustainability activities of stakeholders connected to the organization are coded into a matrix formed of sustainability archetypes and value dimensions. The purpose of this paper is to describe how the SBM framework can be adapted and used for depicting sustainability activities and values annually and over time. In the example used to demonstrate the application of the framework an extra archetype had to be added, which resulted in a modification of the model. By analyzing the adapted and applied matrix, not only which archetypes have the most activity can be seen, but also which stakeholders are involved in initiating, delivering, and capturing of value. The contribution of the paper is to show the applicability and versatility of the developed SBM framework when used in practice. Keywords: Sustainable Business Model (SBM) Framework, Sustainability Activities, Sustainability Archetypes, Value Initiation, Value Delivery, Value Capture, Practical application.